Do personality types make consumers exhibit different complaint behaviors? - Olgun Kitapci; Ibrahim Taylan Dortyol (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2015)
This study aims to explore the differences and similarities in complaint behavior of consumers according to their personality types. 116 managers of a large Turkish finance company have participated in the study. Results show that Intuition-Thinking and Sensing-Thinking individuals tend to engage in public action, while Sensing-Feeling individuals prefer to take private action, and Intuition-Feeling individuals take no action, which is a different form of complaint behavior.
Keywords: M39; M12; 650; Complaint behavior; personality type; Jung's theory; Myers-Briggs type indicator; Turkey